PENGARUH BEBAN KERJA, STRES KERJA DAN KELELAHAN KERJA TERHADAP KINERJA KARYAWAN PADA WARUNG MAKAN BURJO 24 JAM DI AREA SOLO - Desi Kurnia Putri; Kasidin (STIE St. Pignatelli Surakarta, 2021)
This study aims to analyze the effect of workload, work stress and work fatigue on employee performance at a 24-hour burjo food stall in the Solo area. This research was conducted at several 24-hour burjo food stalls in the Solo area. This study used a sample of 95 employees. The sampling method uses probability sampling, namely the simple random sampling method. and the data used are primary data obtained from distributing questionnaires to respondents. The data that has been obtained is processed with the SPSS program using several variables, namely workload, work stress, work fatigue and employee performance. The results showed that the workload had a negative and significant effect on employee performance, this can be seen from the t value of -6.597. Job stress has a positive and significant effect on employee performance, this can be seen from the t value of 0.353. Job fatigue has a negative and significant effect on employee performance, this can be seen from the t value of -7.549.